2023
DOI: 10.1021/jacs.2c13159
|View full text |Cite
|
Sign up to set email alerts
|

s-Indacene Revisited: Modular Synthesis and Modulation of Structures and Molecular Orbitals of Hexaaryl Derivatives

Abstract: Though s-indacene is an intriguing antiaromatic hydrocarbon of 12 π-electrons, it has been underrepresented due to the lack of efficient and versatile methods to prepare stable derivatives. Herein we report a concise and modular synthetic method for hexaaryl-s-indacene derivatives bearing electron-donating/-accepting groups at specific positions to furnish C 2h -, D 2h -, and C 2v -symmetric substitution patterns. We also report the effects of substituents on their molecular structures, frontier molecular orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…During the course of this study, Cheng and Tobe et al reported a series of substituted hexaaryl-s-indacenes with C 2h , D 2h , and C 2v symmetries, as evidenced by X-ray measurements and calculations at the B3LYP level. [26] We computed the symmetrically substituted hexaxylyl-s-indacene (compound 1 f in reference 26) and found that while hexaxylyl-s-indacene exhibits a D 2h s-indacene core at the B3LYP level, minimum geometries at the M06-2X, ωB97X-D, and M11 levels show a C 2h s-indacene core. Computed proton chemical shifts based on M11 geometries give the best match with experiment (Figure 2).…”
Section: Zuschriftenmentioning
confidence: 99%
“…During the course of this study, Cheng and Tobe et al reported a series of substituted hexaaryl-s-indacenes with C 2h , D 2h , and C 2v symmetries, as evidenced by X-ray measurements and calculations at the B3LYP level. [26] We computed the symmetrically substituted hexaxylyl-s-indacene (compound 1 f in reference 26) and found that while hexaxylyl-s-indacene exhibits a D 2h s-indacene core at the B3LYP level, minimum geometries at the M06-2X, ωB97X-D, and M11 levels show a C 2h s-indacene core. Computed proton chemical shifts based on M11 geometries give the best match with experiment (Figure 2).…”
Section: Zuschriftenmentioning
confidence: 99%
“…To the best of our knowledge, no studies have examined the substituent effects in antiaromatic compounds. 11 In this study, we synthesized homoHPHAC monocations and trications with various substituents and investigated their effects on the optical, redox, and geometrical properties and para(dia)tropicity of a series of homoHPHAC mono(tri)cations. Friedel-Cras-type reactions were used to enable the introduction of various substituents.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description by Breslow in 1967, antiaromaticity has been one of the most attractive concepts to describe the electronic features of cyclic π-conjugated molecules. Unlike aromaticity, antiaromaticity gives rise to destabilization, π-bond localization, paratropic ring current, and a decrease in the highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) energy gap in the π-conjugated system . These electronic properties have attracted interest for their utility in advanced organic materials. One interesting topic of study in antiaromatic molecules involves the interconversion of single and double bonds through a process called bond-shift valence tautomerization. An antiaromatic molecule distorts toward a lower-symmetric structure with pronounced bond length alternation (BLA) to avoid the electronic instability caused by π electron delocalization.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the accessible high-symmetric structure should fuel rich insights into the electronic properties driven by its pronounced antiaromaticity or open-shell character (Figure B). Incorporation of quinoidal subunits into the 4 n π-conjugated circuit provides a possible design guide for reducing the barrier for bond-shift valence tautomerization. ,, From this perspective, we have recently focused on diareno­[ a , f ]­pentalenes and disclosed the interrelation between their antiaromatic and open-shell characteristics, , showing hole transport behavior . In a series of diareno­[ a , f ]­pentalenes 1 – 5 (Figure A), the following two principles that govern the interrelation between the antiaromatic and open-shell characteristics are derived: (1) the mode of the embedded o -quinoidal moiety and (2) the formal molecular symmetry of the ring fusion pattern.…”
Section: Introductionmentioning
confidence: 99%